COMPARISON OF 2013 CURRICULUM AND THE DRIVE SCHOOL CURRICULUM REVIEWED FROM STANDARD CONTENTS OF INDONESIAN LESSONS - Mutmainna Mutmainna; Sitti Rabiah; Nurmiah Muin (Citra Dharma Cindekia, 2022)
The curriculum is something that must exist in every component of learning because the curriculum is used as a reference for the success or failure of an educational institution in carrying out the learning process. The purpose of the study was to find out about the 2013 curriculum and the driving school in Indonesian class X subjects in terms of content standards and a comparison of the 2013 curriculum and the driving school curriculum in terms of content standards in the Indonesian class X subjects. The results showed that the 2013 curriculum had a similar concept. good in the educational process, however, implementation in schools is not fully running properly. Meanwhile, the implementation of the driving school curriculum was carried out in the first year quite well. Based on this description, the implementation of the 2013 curriculum is better, but that does not mean that the driving school curriculum is not feasible, only because it has only been implemented this year, so there are still many shortcomings when compared to the 2013 curriculum which has been used for a long time.